Changing attitudes: Women and men’s knowledge of small ruminants’ health in Ethiopia - Wieland, Barbara (International Livestock Research Institute, 2016)
Little information exists on the impact of livestock diseases on different household members. National agricultural researchers were involved in this research, but their capacity on gender was limited. This was an opportunity for them to learn about participatory methods and gender. They used various tools to get information from young and old, men and women. This transformed the way the researchers approached their work. Interview with Barbara Wieland (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net